(untitled) (Journal of Parents and Teachers, 1996)
A constructivist approach is proposed to explore Cervantes’ work, integrating group activities such as dramatizations, crafts and poetry. Students will study the historical and geographical context of the work, encouraging creativity and participation. Assessment will focus on meaningful learning and group collaboration.